1997
DOI: 10.1111/j.1365-2788.1997.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of depression in people with intellectual disability

Abstract: The symptoms of 36 people with varying degrees of intellectual disability (ID) who had had an ICD-10 depressive syndrome in the preceding year were compared with 46 non-depressed people with comparable degrees of ID. Throughout the spectrum of ID, symptoms of depressed affect and sleep disturbance were significantly different between the groups. While symptoms in people with mild ID were reflected in the standard diagnostic criteria, this was not the case in people with moderate and severe ID. With increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
150
4
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 12 publications
5
150
4
1
Order By: Relevance
“…It has been suggested that problem behaviours are behavioural equivalents of depressive symptoms in adults with intellectual disabilities and should be included in diagnostic criteria (Smiley & Cooper, 2003). However, findings have been equivocal on whether problem behaviours should (Charlot et al,1993;Felce et al, 2009;Hurley, 2008;Kishore et al, 2005;Marston et al, 1997;Moss et al, 2000) or should not (Holden & Gitlesen, 2003;Sturmey et al, 2010;Tsiouris et al, 2003;Tsiouris et al, 2011) be considered as depressive equivalents. This creates uncertainty that is reflected in the classification systems, for example problem behaviours are included as symptoms of depression in the DC-LD (Royal College of Psychiatrists, 2001) but not in the DM-ID (Fletcher et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that problem behaviours are behavioural equivalents of depressive symptoms in adults with intellectual disabilities and should be included in diagnostic criteria (Smiley & Cooper, 2003). However, findings have been equivocal on whether problem behaviours should (Charlot et al,1993;Felce et al, 2009;Hurley, 2008;Kishore et al, 2005;Marston et al, 1997;Moss et al, 2000) or should not (Holden & Gitlesen, 2003;Sturmey et al, 2010;Tsiouris et al, 2003;Tsiouris et al, 2011) be considered as depressive equivalents. This creates uncertainty that is reflected in the classification systems, for example problem behaviours are included as symptoms of depression in the DC-LD (Royal College of Psychiatrists, 2001) but not in the DM-ID (Fletcher et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies that have considered problem behaviours as equivalents of symptoms of psychiatric disorders have used a methodology that predefined groups of participants based on whether they met diagnostic criteria for depression that do not include problem behaviours (Charlot et al, 1993;Felce et al, 2009;Holden & Gitlesen, 2003;Hurley, 2008;Kishore et al, 2005;Marston et al, 1997;Moss et al, 2000;Tsiouris et al, 2011). This methodology has limited validity (Ross & Oliver, 2002) because the comparison groups are predefined using diagnostic criteria for depression that do not include problem behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…those in ICD-10 (World Health Organisation, 1992) or DSM-IV (American Psychiatric Association, 1994) (see the retrospective analysis of earlier studies by Pawlarcyzk & Beckwith (1987) and Sovner & Desnoyers-Hurleys (1983); group comparison studies, e.g. Meins (1995) and Marston, Perry & Roy (1997) and a review article by Sturmey (1995)). Hence, these standard diagnostic criteria are regarded as appropriate for use with people with mild or moderate mental retardation.…”
Section: The Presentation Of Depression In People Who Have Mental Retmentioning
confidence: 99%
“…These include informant reports of sleep (Charlot et al, 1993;Marston et al, 1997) and appetite changes (Charlot et al, 1993) and sad/depressed mood (Charlot et al, 1993;Marston et al, 1997).…”
Section: The Presentation Of Depression In People Who Have Mental Retmentioning
confidence: 99%